KNOWLEDGE IMPROVEMENT OF YOUTH ORGANIZATION AND HEALTH’S CADRES OF FIRST AID IN ACCIDENT AT RANGKAH KIDUL VILLAGE - Kusuma Wijaya Ridi Putra; Riesmiyatiningdyah Riesmiyatiningdyah; Meli Diana; Agus Sulistyowati; Faida Annisa; Dini Prastyo Wijayanti; Marlita Dewi Lestari (Community Service Journal of Indonesia, 2020)
First Aid Training in Accidents (P3K) in Youth Organization and Health Care Cadres in Rangkah Kidul Village is one form of community service in the form of counseling aimed at increasing the understanding and skills of the general public towards first aid in accidents. The implementation of these activities on December 7, 2019 took place at the Rangkah Kidul Village Hall, Sidoarjo District, Sidoarjo Regency. The target is Youth Organization and Health Cadre of Rangkah Kidul Village, Sidoarjo. Before the activity is carried out, there is a process of compiling the activity for approximately 2 months before the activity is carried out, starting from determining the theme of the training to applying for permission to the parties concerned. As a form of evaluation, the activity was attended by 28 participants consisting of Health Cadres, Youth Organization, Village Officials, Head of RT / RW, and LKMD representatives. Participants participated in the activity with enthusiasm and seemed very enthusiastic, the training activities could run on time and smoothly. Keywords: Training of the first aid in accident, youth organization, health cadre.